The balance control of children with and without hearing impairment in Singapore - A case study - Jernice, T.; Nonis, Karen; Yi, C. (2011)
The purpose of this study is to compare the balance control of participants with and without HI and also to investigate the effect of a Balance Programme (BP) on their balance control (HI; n = 2, M age = 7 years old). The BP consisted of six practice sessions of 45 minutes each. The Balance Tasks used to assess balance control were static Balance Tasks: two-leg stand, one-leg stand and dynamic Balance Tasks: in-place jump and in-place hop. Kinetic data such as the Centre of Pressure (COP) and the Ground Reaction Force (GRF) was captured using a force plate. The results revealed differences in Balance Tasks involving static and dynamic balance control between participants with HI and without HI. Improvement in balance control of the participants is observed for some of the Balance Tasks after the introduction of the BP which indicates the inconclusive effectiveness of the BP. The authors suggest that the instructional approach and number of practice sessions may be the contributing factors affecting the effectiveness of the BP. A new BP with an alternative instructional approach together with more practice sessions is warranted to benefit both children with and without HI so as to make inclusion possible.